(untitled) (Experimental biology, 2016)
Modern theories of plant diseases prediction are based on results of investigations on laws of pathogenesis and influence of environmental factors on it. Study of genetic basis of plant resistance of soft wheat, search for resistance genes, creation of resistant varieties and their introduction into the breeding practice expands the possibility of preventing the spread of brown leaf rust, one of the most dangerous wheat diseases. The aim of this work is to estimate the influence of brown leaf rust on the elements of productivity and protein content in grain of local varieties of soft wheat Kazakhstanskaya 19, Kazakhstanskaya early and new model object Brachypodium distachyon along with their correlation. The results of the comparative study of the impact of biotic stress on the elements of productivity have shown that Puccinia reconditastatistically significantly reduces the productivity of all parameters in wheat varieties Kazakhstanskaya 19, Kazakhstanskaya early and model object Brachypodium distachyon. The protein content in the grain of wheat of local breeding varieties Kazakhstanskaya 19, Kazakhstanskaya early and wild cereal B.distachyon is not changed when infected with brown leaf rust.